Luminous red galaxies in the Kilo-Degree Survey: selection with broad-band photometry and weak lensing measurements. Issue 3 (8th May 2019) - Vakili, Mohammadjavad; Bilicki, Maciej; Hoekstra, Henk; Chisari, Nora Elisa; Brown, Michael J I; Georgiou, Christos; Kannawadi, Arun; Kuijken, Konrad; Wright, Angus H
ABSTRACT: We use the overlap between multiband photometry of the Kilo-Degree Survey (KiDS) and spectroscopic data based on the Sloan Digital Sky Survey and Galaxy And Mass Assembly to infer the colour–magnitude relation of red-sequence galaxies. We then use this inferred relation to select luminous red galaxies (LRGs) in the redshift range of 0.1 < z < 0.7 over the entire KiDS Data Release 3 footprint. We construct two samples of galaxies with different constant comoving densities and different luminosity thresholds. The selected red galaxies have photometric redshifts with typical photo- z errors of σ z ∼ 0.014(1 + z ) that are nearly uniform with respect to observational systematics. This makes them an ideal set of galaxies for lensing and clustering studies. As an example, we use the KiDS-450 cosmic shear catalogue to measure the mean tangential shear signal around the selected LRGs. We detect a significant weak lensing signal for lenses out to z ∼ 0.7.